Work-family conflict and facilitation profiles of higher education professors: What does influence organizational commitment? - Gelsomini, Elena (2020)
Dissertação de Mestrado em Psicologia do Trabalho, das Organizações e dos Recursos Humanos apresentada à Faculdade de Psicologia e de Ciências da Educação